PROMOTION STRATEGY MEDIA USING TELEVISION, NEWSPAPER, FOR BROCHURE WITH OPTIMAL METHOD TO ACHIEVE PROFITS IN RESTAURANT SIMLEX "NANABAN TEI" - Rijayanih Rijayanih; IRE Puspa Wardhani, SKom, MMSI IRE Puspa Wardhani, SKom, MMSI (Jurnal Sistem Informasi, 2000)
This study contains about promotional strategies undertaken by Nanaban Tei restaurant in promoting the restaurant is using the television media, newspapers, and brochures. With those problems the author explains about how Nanaban Tei restaurant benefit from the promotion. To search for the optimal benefit calculation used with the simplex method.